Juventude, mídia e educação: novas tecnologias e produção de subjetividade em uma escola pública de Fortaleza - Khori, Mauro Michel El (2015)
The present study is a result of an intervention research made in a public school of Fortaleza. The goal is to question the new technologies’ use in a school environment and it’s worthy in the production of subjectivity among students and teachers. This investigation is intended to be contribution in theories and practice of philosophers (or thinkers) like Michel Foucault, Gilles Deleuze and Felix Guattari – especially in its association with subject and subjectivity. The present work has its fundaments in French school of institutional analysis of concepts and tools, as implication, restitution and analyzer, as well as Cartography. It also has its fundaments in Paula Sibilia in order to understand school as a technology of our time, living in a controlling society which produces subjects in a context of institutional conflict between disciplinary practices and connected youth. The research has made use of video making with eleven participants, as well as field observations and informal conversation with students and educators. Three restitutions happened along the process, the last one happening among school educators. Video cameras and photo shoots were used for data recording. Videos are now tools of research producing data and reality changing. As cartography base intervention research, the study is taken as a “research with”, which prioritizes the process and the singular connection among researchers, school and researched subjects. The results points out to some analyzers’ work that were incorporated to the research along the process. Those analyzers highlighted the tension between youth connectivity and institutional availability in providing access to new resources of technology and to the kind of youth consume appropriation and media products through the duality teacher-student. Smartphones came as a main tool in the data acquisition, like a personal and portable gadget with multiple uses which are able to keep the youth permanently connected. The study problematized the way school new technologies are linked to power-resistance relationships, intensifying the culture watch and control. Hyper-connectivity and virtual communication – especially through social media use – are present in the school environment, being a great agent of production of subjectivity and a tool for other socializing forms in a targeted school, where personal information are made public as a fundamental format of relationship among the youth.